Use of plastic primer container covers as effective plug molds for pulsed-field gel electrophoresis - Chua, K.H.; See, K.H.; Puthucheary, S.D. (2009)
Plug molds used for PFGE can be expensive to purchase and often physically and experimentally inflexible. The use of plastic primer container covers as plug molds for Pulsed-Field Gel Electrophoresis (PFGE) is reported in this study. These plastic covers are cheap, effective and easy-to-use for processing samples for electrophoresis. Besides, the broad surface and flat area in the mold promotes faster cooling and the agar sets quickly at room temperature. Plugs are also easily removed with a spatula. These containers can be easily cleaned for re-use or disposed of as waste. Twenty samples can be prepared in one container. The PFGE results obtained by using these plastic primer-container covers as plug molds are similar to the PFGE results obtained by using commercial plug molds.